The Incidence of Portal Vein Thrombosis At Liver Transplantation - Toshiaki Nonami; Itsuo Yokoyama; Shunzaburo Iwatsuki; Thomas E. Starzl (1992)
The incidence of portal vein thrombosis was examined in 885 patients who received orthotopic liver transplantations for various end-stage liver diseases between 1989 and 1990. The thrombosis was classified into four grades. Grade 1 was thrombosis of intrahepatic portal vein branches, grade 2 was thrombosis of the right or left portal branch or at the bifurcation, grade 3 was partial obstruction of the portal vein trunk, and grade 4 was complete obstruction of the portal vein trunk. Among the 849 patients without previous portosystemic shunt, 14 patients (1.6%) had grade 1, 27 patients (3.2%) had grade 2, 27 patients (3.2%) had grade 3 and 49 patients (5.8%) had grade 4 portal vein thrombosis. The incidence of portal vein thrombosis was highest (34.8%) in the patients with hepatic malignancy in the cirrhotic liver, followed by those with Budd-Chiari syndrome (22.2%) and postnecrotic cirrhosis of various causes (15.7%). The patients with encephalopathy, ascites, variceal bleeding, previous splenectomy and small liver had significantly higher incidences of portal vein thrombosis than the others. The total incidence of portal vein thrombosis among the 36 patients with previous portosystemic shunt was 38.9%, which was significantly higher than that (13.8%) of those without shunt.